Adiabene and Hatra: Some Remarks on Hatra’s Neighbor - Marciak, Michał (Anabasis. Studia Classica et Orientalia, 2015)
The article reviews the book “Hatra. Politics, Culture and Religion between Parthia and Rome,” edited by L. Dirven and published in 2013 by Franz Steiner Verlag as volume 21 of the well-known series Oriens et Occidens. It is acknowledged that the book offers the latest research on Hatra. The aim of this article is to contribute to the research on Hatra by taking a look at the regional perspective. Specifically, it is argued that the available sources do not allow us to make far-reaching conclusions about the Roman influence in the neighboring kingdom of Adiabene in the times of Trajan and Septimius Severus. Thus, there was never a “Roman Adiabene” as a province or client kingdom of the Roman Empire. In this sense, both Hatra and Adiabene were integral parts of the Parthian Commonwealth. Furthermore, it is stressed that Hatra and Adiabene had good political and close cultural ties throughout most of the second and early third centuries CE, as they apparently shared the same international challenges and perhaps even the same enemies. In addition, it is likely that both kingdoms mutually profited from transregional trade in the region.